ARSENIC: A HARMFUL AND DESECRATE COMPOUND FOR THE HUMANS - SURESH CHANDRA; ARYENDU KUMAR SAINI; AKASH KUMAR GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Arsenic toxicity has become a burgeoning concern as several millions of people are exposed to this chemical through drinking water contamination by arsenic remains a major public health problem. Acute and chronic arsenic exposure through drinking water has been reported in many countries of the world, where a large proportion of drinking water is contaminated with high concentrations of arsenic. As contamination in groundwater has been found in more than 105 countries around the world, it has become the worldwide health problem as several millions of people are exposed to this toxicant. Arsenic contamination of different countries includes Bangladesh, India, Vietnam, Nepal, Thailand, and Chili is the major affected countries where inorganic arsenic in the groundwater with high concentration is seen. Arsenic is one of the most toxic metals which is originated from the natural environment. The catastrophe is that the majority of human arsenic toxicity is from polluted drinking water rather than agricultural sources (fertilizers or pesticides). The different areas across the Gangetic plains in Nepal and India also recently reported being affected by the arsenic. The hippocampus is a part of the limbic system that is crucial to memory function and spatial navigation. Hippocampus lesions in humans produce devastating impairments in declarative memory, and similar results have been seen in non-human primates with hippocampus neurobehavioral disorders.